Maintenance of inflorescence size variability within common buckwheat (Fagopyrum esculentum Moench) cultivars of various origin: the phenomenon and its possible causes - A. N. Fesenko; I. N. Fesenko; O. V. Biryukova (Труды по прикладной ботанике, генетике и селекции, 2024)
Background. Intrapopulation polymorphism usually can be interpreted as a result of balancing selection, but the basic mechanisms of such selection are not always clear. Earlier we documented a wide variation in the inflorescence size within one of the most genetically uniform common buckwheat (Fagopyrum esculentum Moench) cultivar ‘Skorospelaya 86’, with larger sizes controlled by recessive alleles of multiple genes. The objective of the present work was to analyze the variation within a set of buckwheat cultivars representing different morphological types of the crop, and try to make out possible mechanisms that underlie it. Material and methods. A set of buckwheat cultivars of various origin and belonging to different morphological types were analyzed. The size of inflorescences was assessed as a number of their iterative subunits, i.e., partial floret clusters (PFCs). The number of mature seeds in the entire inflorescence and various PFCs was also counted. Results and conclusions. All the cultivars were variable, with the range at the species level from 6 to 24 PFCs. Accumulation of the genes determining a larger inflorescence seems to be simply explained: larger inflorescences tended to produce more seeds than smaller ones. However, it is not so easy to explain the maintenance of the inflorescence size variability, i.e., why the alleles determining small inflorescences were not lost during the artificial selection for higher seed productivity. Probably, such polymorphism may be useful for maintaining heterosis at the population level.